Efficient ab initio quantum mechanical simulations of structural stability and vibrational properties of bulk, monolayer and (n, 0) nanotubes: Yttrium sesquioxide Y2O3. (10th November 2019) - Larbi, Tarek; El‐Kelany, Khaled E.; Doll, Klaus; Amlouk, Mosbah
Abstract: In this contribution, we report reliable ab initio quantum mechanical simulations of a variety of physical properties concerning yttrium sesquioxide (Y2 O3 ) in different arrangements from the bulk, the monolayer ( h ‐Y2 O3 ), to the ( n, 0) single‐walled nanotubes in the range from n = 6 to 32, for geometry optimization and vibrational properties. Structural parameters, phonon wavenumbers, infrared (IR) and Raman intensities, and elastic constants are computed via density functional theory (DFT/B3LYP) where the trend towards the ( h ‐Y2 O3 ) monolayer for large nanotube radius is discussed. We firstly report combined experimental and computational studies on the structural and vibrational properties of the bulk Y2 O3 . Then, IR and Raman spectra of all arrangements are simulated via the coupled perturbed Hartree–Fock and Kohn–Sham (CPHF/KS) computational schemes. For the ( n, 0) Y2 O3 nanotube family, two sets of IR active phonon modes in the (200–400 cm −1 ) and (600–900 cm −1 ) ranges are determined. Both of them tend smoothly with different slope, towards the optical vibrational modes of the h ‐Y2 O3 single layer. Three sets of active phonon bands are obtained in their Raman spectrum. The first one, in the 0–100 cm −1 range contains two phonon modes, their vibration wavenumbers tend to zero at very large tube radius and are found to be connected to the elastic constants C11 and C66 of the h ‐Y2 O3 monolayer as the 1D → 2D transition is approached. The second one, in 200–400 cm −1 range tends to the optical mode E ′ ( ν = 308 cm −1 ) of the monolayer. The third set, in the 600–900 cm −1 range contains two active modes, their intensities tend to zero in the limit of large nanotube without change in their vibration wavenumbers. Abstract : Using a combination of experiment and quantum mechanical simulations, the structural and vibrational properties of Y2 O3 have been assessed. IR and Raman spectra of Y2 O3 nanoarrangements ranging from two‐dimensional (2D) monolayer to one‐dimensional (1D) semiconducting single walled (n, 0) nanotubes are simulated via the CPHF/KS schemes. These results provide information for the design of yttrium sesquioxide monolayer and nanotube for optoelectronic devices, by better understanding and utilizing their phonon vibration dynamics.